2019
DOI: 10.1074/jbc.ra119.007682
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of resistance of mutant RET protein-tyrosine kinase to its inhibitors nintedanib and vandetanib

Abstract: Edited by Xiao-Fan WangRET is a transmembrane growth factor receptor. Aberrantly activated RET is found in several types of human cancer and is a target for treating RET aberration-associated cancer. Multiple clinically relevant RET protein-tyrosine kinase inhibitors (TKIs) have been identified, but how TKIs bind to RET is unknown except for vandetanib. Nintedanib is a RET TKI that inhibits the vandetanib-resistant RET(G810A) mutant. Here, we determined the X-ray co-crystal structure of RET kinase domain-ninte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 40 publications
0
53
1
Order By: Relevance
“…Although there have been single-case reports of RET V804M and RET S904F mutations conferring resistance to the MKI vandetanib in patients, 18,19 and we recently reported the ability of selpercatinib to overcome both hereditary and acquired RET V804M gatekeeper mutation in patients, 17,18 this report of G810 solvent front mutations provides the first description of acquired, "ontarget" resistance to selective RET inhibition in patients (previous studies have identified RET solvent front mutations in preclinical models of resistance to MKIs, [22][23][24] but not in patients and not with selective RET TKIs). A limitation of this study is the relatively small cohort of patients with acquired resistance studied, and it is likely that activation of bypass signaling and other mechanisms of resistance to selective RET TKIs will be identified through analyses of additional progression biopsies.…”
Section: Discussionmentioning
confidence: 82%
“…Although there have been single-case reports of RET V804M and RET S904F mutations conferring resistance to the MKI vandetanib in patients, 18,19 and we recently reported the ability of selpercatinib to overcome both hereditary and acquired RET V804M gatekeeper mutation in patients, 17,18 this report of G810 solvent front mutations provides the first description of acquired, "ontarget" resistance to selective RET inhibition in patients (previous studies have identified RET solvent front mutations in preclinical models of resistance to MKIs, [22][23][24] but not in patients and not with selective RET TKIs). A limitation of this study is the relatively small cohort of patients with acquired resistance studied, and it is likely that activation of bypass signaling and other mechanisms of resistance to selective RET TKIs will be identified through analyses of additional progression biopsies.…”
Section: Discussionmentioning
confidence: 82%
“…1,7 Structurally, this is partly because these TKIs are known or predicted to occupy both the front and back drug-binding clefts of the RET kinase domain by going through the gate that separates these two clefts. [8][9][10][11][12] Selpercatinib [13][14][15] and pralsetinib 16 are two highly selective and potent RET TKIs. Recently, selpercatinib received the United States Food and Drug Administration (FDA) approval for treating metastatic RET fusion-positive nonsmall-cell lung cancer (NSCLC), advanced/metastatic RET-altered medullary thyroid cancer (MTC), and papillary thyroid carcinoma, while pralsetinib was approved by the FDA for treating RET fusion-positive NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Active site residues, which exist in the hydrophobic region (highlighted as lines in the Figure 1 b), appear to form hydrophobic interactions with the highly potent compound 25 . The part of ligand with an isoxazole moiety was docked inside the hydrophobic pocket, which formed hydrophobic interactions with residues Leu730, Ala756, Val804, and Tyr806, among which Val804 is a gatekeeper residue [ 21 ]. The fused ring was also in a close proximity of hydrophobic residues Ala807, Gly810, Ser811, and Leu881, forming hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%